2014
DOI: 10.2147/ijn.s65567
|View full text |Cite
|
Sign up to set email alerts
|

Multiwalled carbon nanotubes induce altered morphology and loss of barrier function in human bronchial epithelium at noncytotoxic doses

Abstract: Multiwalled carbon nanotubes (MWCNTs) have seen increasing application in consumer products over the past decade, resulting in an increasing risk of human exposure. While numerous toxicological studies have been performed using acute high doses of various carbonaceous nanomaterials, the effects of longer-term, low doses of MWCNTs remain relatively unexplored. This study examined bronchoscopy-derived healthy human bronchial epithelial cells exposed in submerged culture to noncytotoxic doses of MWCNTs over 7 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
24
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 28 publications
(30 reference statements)
6
24
0
Order By: Relevance
“…Specifically, previous studies showed that NDs functionalized with O-containing groups (either -OH or -CO 2 H groups) might lead to complex membrane–particle interactions [54] and their non-specific binding or clustering on the cationic sites of the plasma membrane, with subsequent endocytosis through a temperature-, energy-, and clathrin-dependent pathway [5457]. The uptake of NDs is in contrast with both the uptake of SW- and MWCNTs respectively shown to lead to membrane damage, association with cytoskeleton structures and increased disruption of cellular integrity and organelles upon their translocation [18, 58]. …”
Section: Discussionmentioning
confidence: 99%
“…Specifically, previous studies showed that NDs functionalized with O-containing groups (either -OH or -CO 2 H groups) might lead to complex membrane–particle interactions [54] and their non-specific binding or clustering on the cationic sites of the plasma membrane, with subsequent endocytosis through a temperature-, energy-, and clathrin-dependent pathway [5457]. The uptake of NDs is in contrast with both the uptake of SW- and MWCNTs respectively shown to lead to membrane damage, association with cytoskeleton structures and increased disruption of cellular integrity and organelles upon their translocation [18, 58]. …”
Section: Discussionmentioning
confidence: 99%
“…In C57BL6 female mice, SWCNT exposure results in epithelial-derived fibroblasts composing almost half of the fibroblast population in the lung, demonstrating that epithelial-derived fibroblasts contribute significantly to CNT-induced pulmonary fibrosis 50 . In vitro studies of human epithelial cells treated with low doses of MWCNTs demonstrate an altered morphology of epithelial cells towards a mesenchymal cell phenotype 93 . Analysis of epithelial or mesenchymal specific markers E-cadherin, vimentin, α-SMA, and fibronectin protein expression can clarify the extent of differentiation of the epithelial-derived fibroblasts in EMT in human bronchoalveolar cells 93 .…”
Section: Mechanisms Of Cnt-induced Fibrosismentioning
confidence: 99%
“…Prior studies have demonstrated that CNTs may interfere with the cytoskeleton in HeLa, mast, and bronchial epithelial cells by forming bundle with F-actin filaments [20][21][22]. Thus, we examined if exposure to HCNTs altered F-actin and Arp2 distribution in RAW 264.7 macrophages.…”
Section: Distribution Of F-actin In Raw 2647 Macrophages Following Ementioning
confidence: 95%
“…Another study showed that SWCNTs altered the distribution of the actin cytoskeleton and clathrin in mast cells [21]. Furthermore, a separate study showed that multi walled CNTs (MWCNTs) altered both F-actin and tubulin expression and distribution in human bronchial epithelial cells [22]. Collectively, these studies suggest that CNT exposure results in alteration of F-actin distribution and/ or expression but this may be dependent on specific types of purified CNTs and cell lineages used.…”
Section: Introductionmentioning
confidence: 99%